Geodetic exploitation of the 2014-2015 Bardarbunga unrest: volume variation history and lava tube evolution - Rossi, Cristian; Pedersen, Gro; Dumont, Stephanie; Dirscherl, Mariel Christina (2016)
On August 31, 2014, the main effusive eruption started at Holuhraun in the on the Flædur flood plain (central Iceland), located ~6km north of Vatnajökull glacier and 47 km north east of the Bardarbunga ice-covered caldera, source of the Holuhraun eruption. The activity was declared finished on February 27, 2015, thus lasting for about 6 months. During these months the dyke feeding the eruption kept extracting the magma from the chamber located below the caldera causing the rare event of a gradual caldera collapse. In this context and because of the difficult access conditions of the Icelandic highlands, TanDEM-X remote sensing data is of particular interest. By producing high-resolution and accurate elevation models, TanDEM-X data allow quantification of elevation and volume changes observed within the volcanic system during the eruption. This study focuses on the space-time evolution of the Bardarbunga caldera collapse and the evolution of closed lava pathways in the Holuhraun lava field. It provides a unique opportunity to better characterize and understand the physical processes behind these topographical changes. A stack of thirteen DEMs is employed for the caldera monitoring and imaging of the northwestern portion of the Vatnajökull glacier. The caldera volume loss has been temporally tracked, up to the final measured loss of about 1.4 cubic kilometers. Moreover, the dyke propagation from Bardarbunga to the Holuhraun lava field has been derived and a graben structure with a width of up to 1 km and a sinking of a few meters has been measured. A second stack of nine DEMs over the Holuhraun area has also been generated. This data stack covers the last stage of the eruption, allowing the characterization of a lava field, which was dominated by the gradual development of closed lava pathways. The areas of uplift have been precisely localized and the volume estimates for this phase of the eruption have been derived, thus getting a more detailed picture of the closure of the eruption and its space-time evolution ...